Deconstruction of Women’s Testimony in Fiqh: Promoting Gender Equality in Hilal Sighting Through Sociological and Astronomical Perspectives - Nurkhanif, Muhammad (Islamic Studies Review, 2025)
This study aims to deconstruct the traditional views in Islamic jurisprudence regarding women's testimony in the determination of the beginning of lunar Islamic calendar months, by examining gender equality through the perspective of the sociology of change and Islamic astronomy. This process, which has traditionally involved more men than women, is revisited with consideration of the role of women in contemporary society. In Islam, both men and women have equal capacity to provide testimony in various matters. Advances in science and technology have increasingly blurred the distinctions between men and women, as evidenced by the equal opportunities and positions in social, cultural, structural, and even religious domains. Unfortunately, women's involvement in moon sighting (rukyat al-hilal) remains very limited. In fact, in the history of the Ministry of Religious Affairs' decisions on the confirmation (istbat) of the new moon for the beginning of Ramadan, Shawwal, and Dhu al-Hijjah, there has only been one accepted and recorded testimony from a woman in the official decree of the Ministry of Religious Affairs (KMA). This raises a significant question: is there a restriction on women's participation in rukyat al-hilal activities due to their social status? This study highlights how social dynamics and developments in knowledge, particularly Islamic astronomy, can drive a more inclusive reinterpretation of Islamic law. The research employs a qualitative method with a descriptive and critical analysis using the sociology of change and Islamic astronomy in the process of deconstruction. This study also explores how gender equality can be realized in religious practices and its implications for the reform of Islamic law. The findings of this study include the formulation of women's testimony in rukyat al-hilal and its validity compared to men's testimony.